A new way of teaching programming skills to K-12 students: Code.org - Kalelioğlu, Filiz (Computers in human behavior, 2015)
•The aim of this study is to investigate the effects of programming with code.org site on reflective thinking skills towards problem solving.•Programming with code.org site did not cause any differences in reflective thinking skills toward problem solving.•Students developed a positive attitude towards programming.•Female students showed that they were as successful as the male students. This study attempts to investigate the effect of teaching code.org site on reflective thinking skills towards problem solving. More specifically, this study attempts to investigate whether there is a gender difference in terms of students’ reflective thinking skills towards problem solving. This triangulation study was conducted with 32 primary school students. The quantitative part of the study was conducted in pre-test/post-test comparison design of quasi-experimental design. The scores of reflective problem solving skills were gathered through the reflective thinking skill scale towards problem solving and the students’ performances in the code-org site were examined. In the qualitative part of the research, after the five-week experimental process, focus group interviews were conducted with ten students and a reflection paper from the IT teacher was analysed. According to the t-test results, teaching programming to primary school students in the code.org site did not cause any differences in reflective thinking skills towards problem solving. However, there is a slight increment in the means of female students’ reflective thinking skills towards problem solving over the males’ reflective thinking skills towards problem solving. On the other hand, qualitative data provided more information about the students’ experiences. Students developed a positive attitude towards programming, and female students showed that they were as successful as their male counterparts, and that programming could be part of their future plans.